Studi Kualitatif Tentang Faktor-Faktor Protektif Pada Anak Dengan Dyslexia - Febrina Della; Sri Nurhayati Selian (Peneliti.net, 2026)
Dyslexia is a specific learning disorder characterized by difficulties in reading, spelling, and understanding written text. This condition may affect children's academic, emotional, and social development. However, some children with dyslexia are able to adapt positively despite their learning difficulties. This study aims to explore the protective factors that help children with dyslexia cope with their learning challenges. This research employed a qualitative approach with a phenomenological design. The participants were children aged 8–15 years who had been identified as having dyslexia. Participants were selected using purposive sampling. Data were collected through in-depth interviews, observations, and documentation. The data were analyzed using thematic analysis. The findings revealed four main protective factors that support children with dyslexia: family support, support from teachers and the school environment, adaptive learning strategies, and children's self-confidence and personal motivation. Support from family and teachers plays an important role in creating a positive and inclusive learning environment, while adaptive learning strategies and self-confidence help children overcome their reading difficulties. The results highlight the importance of collaboration between families and schools in supporting the development of children with dyslexia